2020
DOI: 10.36103/ijas.v51i1.933
|View full text |Cite
|
Sign up to set email alerts
|

Response of Pomegranate " Cv. Wonderful" Transplants to Mineral Nutrition and Gibberrelic Acid

Abstract: This study was aimed to investigate response of pomegranate " Cv. Wonderful" transplants to mineral nutrition and gibberellic acid, it was conducted at the Coll. of Agriculture Engineering Sciences-University of Baghdad, a factorial experiment was according to R.C.B.D. with three replicates for two consecutive growth seasons 2018-2019 to addition six treatments of nue tharyan fertilizer (N.P.K. 20:20:20 and some micronutrients) with three concentrations (0, 2.5, 5 gm.L-1) for  each of the soil fertilization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…15 show the effect of the interactions between treatments and storage period, the significant differences were observed among them, also found that the highest value (19.52%) of anthocyanin content in fruits immersed in 1% flaxseed oil which stored for the two months, while the lowest value (9.36%) was found from fruits treated with 0.5% flaxseed oil which stored for the three months Visual evaluation (%): From the Fig. 16 the results indicated that all treatments were significantly superior to maintaining the quality of the fruits than uncoated fruits and 0.5% flaxseed oil, the fruits coated with 1% chitosan were significantly superior to the other treatments, which got the highest percentage (3.99%). While the lowest percentage was recorded in uncoated fruits.…”
Section: Fig 13 Effect Of Flaxseed Oil Black Seed Oil and Chitosan Co...mentioning
confidence: 86%
See 1 more Smart Citation
“…15 show the effect of the interactions between treatments and storage period, the significant differences were observed among them, also found that the highest value (19.52%) of anthocyanin content in fruits immersed in 1% flaxseed oil which stored for the two months, while the lowest value (9.36%) was found from fruits treated with 0.5% flaxseed oil which stored for the three months Visual evaluation (%): From the Fig. 16 the results indicated that all treatments were significantly superior to maintaining the quality of the fruits than uncoated fruits and 0.5% flaxseed oil, the fruits coated with 1% chitosan were significantly superior to the other treatments, which got the highest percentage (3.99%). While the lowest percentage was recorded in uncoated fruits.…”
Section: Fig 13 Effect Of Flaxseed Oil Black Seed Oil and Chitosan Co...mentioning
confidence: 86%
“…) is an economically important crop with great nutritional value (22). Considering its importance many researchers focused on improving its productivity and quality, the pomegranate fruits are considered nonclimacteric (16,20). It is necessary to harvest fully ripened fruits; pomegranate fruits are very sensitive to storage conditions, as this causes fruit spoilage, weight loss and chilling injury (29).…”
Section: ‫العراقية‬ ‫الزراعية‬ ‫العلوم‬ ‫مجلة‬mentioning
confidence: 99%